IMPROVING THE SYSTEM OF MATERIAL REWARDING EMPLOYEES OF EDUCATIONAL INSTITUTIONS - Isxakova S. A. (Scholar Express Journals, 2022)
This article examines the effectiveness of the system of remuneration of professors and teachers of higher education institutions and develops scientific recommendations for improving the system of incentives for their work.
Keywords: Higher education; labor motivation; wages; incentives